ANALISIS FAKTOR LOKASI, KELENGKAPAN PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK DAGING SAPI DAN TURUNANNYA - Agung Muhammad Firdaus; Achmad Firman; Anita Fitriani (Universitas Galuh, 2022)
The purpose of the study was to determine the effect of location, product completeness, and price, either partially or simultaneously on purchasing decisions for beef products and their derivatives. The research method was a survey of 42 respondents using a questionnaire as a tool. The data obtained were analyzed using ordinal regression analysis. The results showed that there was a partial effect of location and price, while the completeness of the product did not partially influence the decision to purchase beef and its derivatives at Ciwastra Traditional Market; and all factors simultaneously influence the decision to purchase beef and its derivatives at Ciwastra Traditional Market with a model accuracy of 56%.